Hubungan Perilakuteman Dan Stres DenganPerilaku Merokok Pada Remaja Di KelurahanDukuh, Sukoharjo - Kurniawan, Dian; , Abi Muhlisin, SKM, M.Kep (2016)
Smoking is one of the biggest concerns facing the world health as it can lead to nearly six million people die within a year. Existing health problems in Indonesia related to lifestyle changes, such as changes in eating habits, smoking, substance abuse, lack of activity, and others. Although tobacco use by sucking, chewing, inhaling, and others, there is no safe way to use tobacco. Various types of cigarettes smoked or used tobacco without burned, can be detrimental to health when used above a certain threshold and used repeatedly. Health problems due to smoke caused by chemicals contained in cigarettes or in which tobacco use. The aim of research to determine of friends and stress and smoking behavior in adolescents in Dukuh village, Sukoharjo. Penelitiaan method used is descriptive correlational cross-sectional design. The population of this study adolescents who smoke and live in Dukuh village, Sukoharjo as many as 50 people with a total sampling technique. The independent variable in the form of the friends and the stress while the dependent variable smoking behavior, the instrument used by the questionnaire. Data analysis techniques to the analysis Fisher. The results showed that most respondents have a strong of friends who belong to as many as 27 respondents (54.0%), most respondents viewed from the relatively strong influence of stress as many as 29 respondents (56.0%), most of the respondents have good behavior as many as 36 respondents (50.7%), there is a significant relationship with the friends influence smoking behavior in adolescents in Dukuh village, Sukoharjo (p = 0.000), and there is a relationship signifi9kan influence of stress and smoking behavior in adolescents in the Village Hamlet, Sukoharjo (p = 0.002). It is advisable for teens more active and thorough in seeking information from a variety of existing media, so the teens have the insight and understanding of the behavior of health high in order to avoid risks impact of smoking behavior.